Responses of the Black Fungus Cryomyces antarcticus to Simulated Mars and Space Conditions on Rock Analogues - Claudia Pacelli; Laura Selbmann; Laura Zucconi; Claudia Coleine; Jean-Pierre de Vera; Elke Rabbow; Ute Bottger; Ekaterina Dadachova; Silvano Onofri (Astrobiology, 2019)
This is the final paper "Responses of the Black Fungus Cryomyces antarcticus to Simulated Mars and Space Conditions on Rock Analogues" Published in ASTROBIOLOGY Volume 19, Number 1, 2019,DOI:10.1089/ast.2016.1631 https://www.liebertpub.com/doi/10.1089/ast.2016.1631 Funded by the European Space Agency (ESA); Italian Space Agengy (ASI); Italian National Program for Antarctic Researches (PNRA)